Evaluation Of Raw Material Inventory Policies Using Material Requirement Planning (MRP) And Lot Sizing Methods: Case Study Of XYZ MSMEs - Rafsanjana, Sasotya Rigan; Prihardianto, Rahaditya Dimas; Arismawati, Paramaditya (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in economic growth in Indonesia. Inventory management is one of the key aspects in the operational sustainability of MSMEs, especially raw materials used in the production process. One of them is XYZ MSMEs which is a producer of meatball pentol and meatball tofu products which uses several types of raw materials in its production process. The problem currently being faced is that there are often shortages and excesses in purchasing raw materials during procurement. This research aims to analyze the cost of raw material inventory at XYZ MSMEs using five different Lot Sizing methods, namely Economic Order Quantity (EOQ), Period Order Quantity (POQ), Silver Meal (SM), Least Unit Cost (LUC), and Part Period Balancing (PPB). This research uses historical data from MSME XYZ to identify differences in raw material inventory costs between the five MRP methods used. The results of this research show that the Silver Meal (SM) method produces the lowest total inventory costs for beef and tapioca starch as raw materials. Meanwhile, the Part Period Balancing (PPB) method produces the lowest total inventory costs for MSG raw materials.